The Comorbidity of Reduplicative Paramnesia, Intermetamorphosis, Reverse-Intermetamorphosis, Misidentification of Reflection, and Capgras Syndrome in an Adolescent Patient - Ozden Arısoy; A. Evren Tufan; Rabia Bilici; Sarper Taskiran; Zehra Topal; Nuran Demir; M. Akif Cansız (Case Reports in Psychiatry)
Delusional misidentification syndromes may be superimposed on neurological or psychiatric disorders and include delusional beliefs that the people, objects, or places around the patient change or are made to change with one another. In this paper, an adolescent patient displaying Capgras syndrome, metamorphosis, reverse-intermetamorphosis, misidentification of reflection, and reduplicative paramnesia was presented. The findings that our patient struggled with visuospatial tests applied in the acute phase as well as the observation that she refused to meet her family face-to-face while accepting to speak on the phone may support the role of right hemisphere and visuospatial functions in the development of those syndromes. Further studies or case series evaluated more extensively are needed to reveal the relationship between right hemisphere functions and delusional misidentification syndromes.